The function of repeating: The relation between word class and repetition type in developmental stuttering. Issue 2 (24th July 2015) - Buhr, Anthony P.; Jones, Robin M.; Conture, Edward G.; Kelly, Ellen M.
Abstract: Background : It is already known that preschool‐age children who stutter (CWS) tend to stutter on function words at the beginning of sentences. It is also known that phonological errors potentially resulting in part‐word repetitions tend to occur on content words. However, the precise relation between word class and repetition type in preschool‐age stuttering is unknown. Aims : To investigate repetitions associated with monosyllabic words in preschool‐age CWS. Specifically, it was hypothesized that repetition type should vary according to word class in preschool‐age CWS and children who do not stutter (CWNS). Methods & Procedures : Thirteen preschool‐age CWS and 15 preschool‐age CWNS produced age‐appropriate narratives, which were transcribed and coded for part‐word repetitions (PWR) and whole‐word repetitions (WWR) occurring on monosyllabic words. Each repetition type was also coded for word class (i.e., function versus content). Outcomes & Results : Results indicated that although CWS and CWNS were significantly more likely to produce PWR on content words, this tendency did not differ between the two talker groups. Further, CWS and CWNS did not differ in their tendencies to produce PWR versus WWR overall, but the tendency to produce repetitions on function words was significantly greater for CWS versus CWNS. Conclusions & Implications : Findings are taken to suggest that repetitions of monosyllabic words in young children are not easily explained from the perspective of phonological errors, but may instead be considered from an incremental planning of speech perspective.